In Need of Non-Western Education in Western Countries - Steinmetz, Carl Hermann Dino (Advances in Social Sciences Research Journal, 2026)
Increasing cultural diversity within Western societies has generated renewed interest in the role of educational systems in promoting belonging, and social mobility. In the Netherlands, immigrants, refugees, and expatriates continue to experience disproportionate barriers to educational participation and achievement, resulting in educational stagnation, exclusion, and reduced opportunities for social- and economic integration. This article explores whether insights from non-Western educational traditions can contribute to addressing these challenges and inform contemporary debates on educational decolonisation. Drawing upon literature on Indigenous, Confucian, Islamic, and Ubuntu pedagogies, the article examines the philosophical foundations, pedagogical practices, and social objectives of non-Western educational systems and compares them with dominant Western educational traditions. Particular attention is given to differences in conceptions of knowledge, citizenship, socialisation, moral development, and the relationship between the individual and the community. The analysis demonstrates that while Western education has traditionally prioritised individual autonomy, critical thinking, and preparation for democratic and economic participation, many non-Western traditions emphasise relationality, communal responsibility, moral formation, intergenerational learning, and holistic human development. The article argues that the educational difficulties experienced by immigrants, refugees, and expatriates cannot be understood solely through individual or linguistic explanations but must also be situated within broader institutional, cultural, and historical contexts. Decolonising education therefore requires more than symbolic recognition of multiculturality; it necessitates the inclusion of multiple epistemologies and educational traditions within educational policy and practice. The study concludes that educational pluralism, rather than the replacement of one dominant paradigm by another, offers the most promising pathway towards inclusive, culturally responsive, and socially just educational systems in multicultural societies such as the Netherlands.